mstoenzymic study on cervix in prepubertal and induced pubertal local Assam she goat - TALUKDAR, S R; BHATTACHARYA, M; SARMAH, B E (The Indian Journal of Animal Sciences, 2011)
The study was conlducted on cervix from 21 Assam local she goats in prepubertal and exogenous hormonally induced pubertal groups. The prepubertal animals meant for induction were administered PMSG after priming, and ReG just after the onset of estrus. Cervical tissues were collected on day 3 following behavioral estrous exhibition by the animals. The histochemical reaction for Malate dehydrogenase, lactic dehydrogenase, glucose-6- phosphate dehydrogenase 5-3B- hydroxysteroid dehydrogenase, 17B-hydroxysteroid dehyrogenase and cytohrome oxidase were observed significantly in the cervical epithlium of all goats with minor variation in location of enzymes between age groups. The reaction for succinic dehydrogenase in cervical epithelia was not well pronounced in all animals. The presence of these enzymes were not well marked in lamina propria, tunica sub mucosa and tunica serosa; however, tunica muscularis exhibited weak to strong intensity ofreaction at different ages. Â